Relationship between human resource diversity management practices, diversity receptiveness and organizational citizenship behavior / Ahmad Nizan Mat Noor - Mat Noor, Ahmad Nizan (Institute of Graduate Studies, UiTM, 2015)
Organizations today constantly have to discover new ways to be successful and respond to challenges. The employments of workforces who are motivated and willing to exhibit extra role behaviors are important for the survival of the organization. For hotel industry, operational employees must demonstrate such voluntary behaviors in delivering quality services to customers. However, it is becoming more difficult if this type of hotel employees resist exhibiting extra role behaviors or doing something that is beyond the requirement. Therefore, what motivates employees to engage in or exhibit citizenship behaviors has been one of the mainly critical issues faced by hoteliers. While potential factors that could encourage employees’ positive attitudes and behaviors considered being the primary focus of interest to practitioners and academia, perceived justice from the fair treatment they have received from the organization is argued to be a strong motivational indicator for such behavior…